Pengaruh Model Pembelajaran Quantum Teaching terhadap Motivasi Belajar Siswa Mata Pelajaran PAI di SMK Shalahuddin Pasuruan - Siti Aminah, Ika Putri; Halimah, Siti (Tarbiyatuna Kajian Pendidikan Islam, 2026)
This study examines the effect of the Quantum Teaching learning model on students'learning motivation in Islamic Religious Education subjects at SMK ShalahuddinPasuruan, which is motivated by low student learning motivation such as lowparticipation and attendance. The study used a descriptive quantitative approach withan ex-post facto type and a sample of 72 students, the results showed a Pearsoncorrelation of 0.655 and a regression coefficient of 0.412, which means QuantumTeaching is able to increase learning motivation significantly. The R Square value of42.9% indicates that almost half of the variation in student motivation can beexplained by the use of this model. The t-test with t count 7.648 > t table 1.994 and asignificance of 0.000 < 0.05 strengthens the conclusion that Quantum Teaching iseffective in increasing student learning motivation in Islamic Religious Educationsubjects at the SMK.